Preliminary Considerations and Phases of Pakistan Foreign Policy (Journal of Social Sciences Review, 2023)
Like all other states in the world Pakistan is a sovereign and only nuclear Islamic state on the planet. Upon its initial release from the British raj, it faced significant challenges. There was a prevailing belief that it will return to India. During that period, however, the government did implement authentic measures to address the situation in a piecemeal manner. The commencement of the Cold War between the Communist and Capitalist blocs occurred at that juncture. The newly emerging states in the world were joining one or another bloc. Pakistan was also among them. This study highlights the importance placed on foreign policy rules, ideals, and laws. In the subsequent sections, we will delve into a comprehensive analysis of the aforementioned phases, drawing from primary and secondary sources. Pakistan's decision to join the capitalist bloc might be attributed to its worse financial condition compared to India, which compelled it to make these options. However, safety and independence were consistently safeguarded throughout all time periods and stages.
Keywords: Pakistan; Foreign policy; Challenges; Cold War